Pendidikan Akhlak Menurut Az-Zarnuji dalam Kitab Ta’lim al-Muta’allim - Alfianoor Rahman (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2016)
The current educational condition shows lack of attention aboutmoral, the teacher merely transfer the knowledge and the pupils merelyreceive it, there are no attention about the morals, morals toward teachersand fellow pupils. Those state encourage us to build the point of view ineducation field which give the attention about the morals not only educationwith knowledge orientation and skill orientation. This issue had gotten theattention from education figure of muslim since the 12th century. Az-zarnujihad written the book of ta’limul muta’allim which contain the etic of learning.This writing finds that the the book has the sufistic aspect when the conceptof ridha, tawadhu’, wara’, ikhlas and sabr become key of learning process. And inmoral education az-zarnuji uses nasihah method and remainding methodand the required thing in learning (niah, wara’, istifadah and tawakkal).Eventually this writing concluse that the concept of leraning process ofzarnuji is oriented to the values of morals as well as the intellectual valueand skill value.